Sobre grupos abelianos finitamente gerados - Zotti, André Luiz Pereira (2017)
The Group Theory is a branch of Mathematics which studies Algebraic Structures called Group. The methods of Group Theory have strongly influenced various branches of algebra. In Combinatorial Analysis the notion of permutation group from a group is a commonly used to simplify the counting of Objects Set. The Group Theory understanding is key role in Physics. It is used to describe symmetries which Physical Laws must obey. In Chemistry, groups are used to classify crystalline structures and molecules symmetry. In view of what has been exposed here, the objective of the present work was to realize a study on concepts and properties of Group Theory with special reference to Generated finitely abelian Groups. After theories on groups referred above it was proposed some didactic activities to be developed by high school students. Such activities emphasized some properties discussed in high school. The theoretical background was based in following authors (GARCIA, 2003), (GONC¸ ALVES, 2008) and (FRALEIGH, 2000).